Penilaian Keberlanjutan Tempat Pengolahan Sampah 3R Cipacing Resik dengan Metode Multidimensional Scaling - I Made Wahyu Widyarsana; Plucheria Pritta Aquila; Reslisari Rara Massora; Tanjung Mega Dwi Puspita (Jurnal Serambi Engineering, 2024)
Cipacing village is one of the villages where TPS 3R was developed by the West Java Regional Settlement Infrastructure Agency to address the village's waste problems. Over time, TPS 3R Cipacing Resik has faced several waste challenges that could threaten the sustainability of the infrastructure. Research was conducted to assess the sustainability of TPS 3R based on five aspects: regulatory, institutional, financial, community participation and operational technical aspects. Questionnaires were distributed to 30 respondents using a purposive sampling technique and then analysed using the RAPFISH technique. The results of the study indicate that the sustainability index value of TPS 3R Cipacing Resik is 94.99, which is classified as sustainable. However, efforts are needed to improve the financial dimension. As a follow-up to the results of the sustainability assessment, WTP and ATP analyses were conducted on the beneficiaries of the 3R TPS to assess the respondents' willingness to pay for improved waste management services using the CVM. The analysis results showed that the respondents have an EWTP value of IDR 28,500.00/month, a TWTP value of IDR 4,788,000.00/month and an ATP value of IDR 13,300.00/month. This means that the willingness to pay of the community beneficiaries of TPS 3R Cipacing Resik is higher than their ability to pay for waste management services. In addition, the statistical analysis also showed that income factors influence the community's WTP value.